Estrategias didácticas mediadas con TIC para fortalecer aprendizaje autónomo de la matemática en estudiantes de 9° del IDDI Nueva Granada (2014)
To speak about the formation for autonomous learning come up by the TIC, in addition to being an important characterization in the topic of the globalization in the current world, is constituted in a valid way to cultivate and to promote skills in the students to direct their own learning and to acquire major conscience on the way of learning and the factors that can affect in this process; also there is propitiated between its recipients the generation of the self-discipline and the self-regulation in the exercise of the study, like essential dynamics for the continuous progress of its conduct as aprendiente. The present investigation, he tries to reach port in elements that they contribute with the acquisition of one of the goals that looks for the current education, to achieve the autonomous management of learning in the field of mathematics across the TIC on the part of the students, treating that these could use in strategic form the educational resources put at its disposal; in the same way, to think with critical sense and to take decisions if the same bearing in mind several points of view, so much in the moral ambience as the intellectual.